Serum Transferrin Receptors of Iron Deficiency Anemic Rats That Feeding Tempe Fortification Combination Iron and Vitamin A - Rahayu Astuti; Hertanto Wahyu Subagyo; Siti Fatimah Muis; Budi Widianarko (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2016)
Abstract. This research investigated tempe fortified with iron and vitamin A on serum transferrin receptors. Experimental research Randomized Pre Test-Post Test Control Group Design was conducted on 30 Sprague-Dawley rats with iron deficiency anemia. The rats divided into 6 groups randomly, was treated for 6 weeks with a standard feed supplemented by soybean tempe fortified with iron and vitamin A. Group 1 control group was given standard feed AIN93G (SF), group 2 SF+T0, group 3 SF+T1, group 4 SF+T2, group 5 SF+T2+V15, (6) SF+T2+V50. T0 was tempe without fortification. T1 and T2 was tempe that was fortified with 230 ppm and 271 ppm of iron (FeSO47H20, respectively. V15 and V50 was tempe that was fortified with 15 ppm and 50 ppm of vitamin A (retinyl acetate, respectively. Statistical test was used Kruskal Wallis test. The result showed that before intervention, there was no significantly different on mean of serum transferrin receptors (sTfR) (p=0,280). After intervention, sTfR became 13,04,0; 8,72,8; 8,52,6; 7,43,4; 7,21,7 and 1,90,4 g/mL, respectively. Tempe fortification with iron and vitamin A significantly decreased sTfR (p=0,004). Average of sTfR lowest in the treatment of SF+T2+V50 (standard feed+tempe was fortified with 271 ppm of iron + 50 ppm vitamin A).